Directly Attached Bisdonor‐BF2 Chelated Azadipyrromethene‐Fullerene Tetrads for Promoting Ground and Excited State Charge Transfer. Issue 18 (3rd March 2017) - Collini, Melissa A.; Thomas, Michael B.; Bandi, Venugopal; Karr, Paul A.; D'Souza, Francis
Abstract: The efficiency and mechanism of electron‐ and energy‐transfer events occurring in both natural and synthetic donor–acceptor systems depend on their distance, relative orientation, and the nature of the surrounding media. Fundamental knowledge gained from model studies is key to building efficient energy harvesting and optoelectronic devices. Faster charge separation and slower charge recombination in donor–acceptor systems is often sought out. In our continued effort to build donor–acceptor systems using near‐IR sensitizers, in the present study, we report ground and excited‐state charge transfer in newly synthesized, directly linked tetrads featuring bisdonor (donor=phenothiazine and ferrocene), BF2 ‐chelated azadipyrromethane (azaBODIPY) and C60 entities. The tetrads synthesized using multi‐step synthetic procedure revealed strong charge‐transfer interactions in the ground state involving the donor and azaBODIPY entities. The near‐IR emitting azaBODIPY acted as a photosensitizing electron acceptor along with fullerene whereas the phenothiazine and ferrocene entities acted as electron donors. The triads (bisdonor–azaBODIPY) and tetrads revealed ultrafast photoinduced charge separation leading to D .+ –azaBODIPY .− –C60 and D .+ –azaBODIPY–C60 .− (D=phenothiazine or ferrocene) charge separated states from the femtosecond transient absorption spectral studies in both polar and nonpolar solvent media. The charge‐separated states populated the triplet excited state of azaBODIPY prior returning to the ground state. Abstract : Close encounters of the charge transfer kind : Directly connected supramolecular triads and tetrads featuring bisphenothiazine or bisferrocene, azaBODIPY, and C60 have been newly synthesized to demonstrate ground and excited state intramolecular charge transfer.